Genome and physiology of the ascomycete filamentous fungus Xeromyces bisporus, the most xerophilic organism isolated to date. (7th October 2014) - Leong, Su‐lin L.; Lantz, Henrik; Pettersson, Olga V.; Frisvad, Jens C.; Thrane, Ulf; Heipieper, Hermann J.; Dijksterhuis, Jan; Grabherr, Manfred; Pettersson, Mats; Tellgren‐Roth, Christian; Schnürer, Johan
Summary X eromyces bisporus can grow on sugary substrates down to 0.61, an extremely low water activity. Its genome size is approximately 22 Mb. Gene clusters encoding for secondary metabolites were conspicuously absent; secondary metabolites were not detected experimentally. Thus, in its 'dry' but nutrient‐rich environment, X. bisporus appears to have relinquished abilities for combative interactions. Elements to sense/signal osmotic stress, e.g. HogA pathway, were present in X. bisporus. However, transcriptomes at optimal (∼ 0.89) versus low aw (0.68) revealed differential expression of only a few stress‐related genes; among these, certain (not all) steps for glycerol synthesis were upregulated. Xeromyces bisporus increased glycerol production during hypo‐ and hyper‐osmotic stress, and much of its wet weight comprised water and rinsable solutes; leaked solutes may form a protective slime. Xeromyces bisporus and other food‐borne moulds increased membrane fatty acid saturation as water activity decreased. Such modifications did not appear to be transcriptionally regulated in X. bisporus; however, genes modulating sterols, phospholipids and the cell wall were differentially expressed. Xeromyces bisporus was previously proposed to be a 'chaophile', preferring solutes that disorder biomolecular structures. Both X. bisporus and the closely related xerophile, Xerochrysium xerophilum, with low membrane unsaturation indices, could represent a phylogenetic cluster of 'chaophiles'.